How Young Consumers Perceive Vertical Farming in the Nordics. Is the Market Ready for the Coming Boom? - Linthujan Perambalam; Dafni D. Avgoustaki; Aspasia Efthimiadou; Yongming Liu; Ying Wang; Maozhi Ren; Antonios Petridis; George Xydis (Agronomy, 2021)
Producing food via vertical farming (VF) is an efficient method since it requires less space with increased yield per unit area. Such a system can assist in solving major food-shortage problems since it presents a higher crop yield per unit area compared to conventional farming. Thus, VF can be seen as a production method that can cope with the challenge of the constantly growing population, making it also possible to cultivate crops in regions with adverse climate conditions. However, the public might be concerned about the sustainability of VF systems since plants are produced in an unconventional setting. Therefore, there is a need to consider and evaluate the consumers’ acceptance of VF. The particular study attempts to both analyse consumer acceptance of VF in the Nordic areas and offer insights into VF acceptance among young customers in a comparative analysis. The results indicated that VF is not widely accepted by young Nordic consumers. The concept of sustainability is one of the principles driving forces behind consumer acceptance of vertical farms. The more cases of vertical farms in European cities, the better seems to be the level of acceptance among young customers and their willingness to purchase their products.